Causas de ambliopia e resultados do tratamento - Gonçalves, Fernando [UNESP] (2006)
Objective: to evaluate the causes and the results of occlusion amblyopia treatment. Methods: a retrospective study was done including children under 12 years old. Sex, age of starting treatment, etiology, ocular deviation affection, visual acuity and time for the occlusion treatment were evaluated. Results: 158 children had all the requirements to compose the sample. 50.6% were males. 70.2% had esotropia, 13.2% exotropia, 0.7% hypertropia and 4.4% presented horizontal and vertical strabismus. 11.4% had no ocular deviation. 6.6% presented anisometropia, 0.7% congenital cataract and 6.6% other diagnoses. Visual acuity improved in 85.5%, faster in the ortophoric children. The occlusion treatment time was long in all the deviation types. Conclusion: the treatment was beneficial in improving amblyopia in the majority of the children evaluated.